2007
DOI: 10.1007/s10490-007-9037-4
|View full text |Cite
|
Sign up to set email alerts
|

Managers’ conflict management styles and employee attitudinal outcomes: The mediating role of trust

Abstract: This study examines the mediating effects of trust on the relationships between manager's conflict management styles (CMS) and employee attitudinal outcomes, as well as identifies the potential deviations in the areas of CMS and trust from the west in Chinese culture. One hundred sixty-nine employees in Guangzhou of China participated. As predicted, Integrating CMS of managers is found significantly correlated to trust and subordinates' job satisfaction and turnover intention. Trust fully mediates the link bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 53 publications
3
72
0
2
Order By: Relevance
“…In conceptual models Doney et al (1998) propose that trust in intra-and inter-organizational relationships is partly an outcome of cross-cultural issues and Van der Zee et al (2009) argue that perceptions of trust may be influenced by cultural factors that relate to both work group diversity and minority team member views of the organization. Prior studies have shown that trust in organizational settings is imbued with cultural issues (Chan et al, 2008) that can influence perceptions of organizational change, particularly in international acquisitions (e.g. Stahl et al, 2012).…”
Section: Limitations and Implications For Researchmentioning
confidence: 99%
“…In conceptual models Doney et al (1998) propose that trust in intra-and inter-organizational relationships is partly an outcome of cross-cultural issues and Van der Zee et al (2009) argue that perceptions of trust may be influenced by cultural factors that relate to both work group diversity and minority team member views of the organization. Prior studies have shown that trust in organizational settings is imbued with cultural issues (Chan et al, 2008) that can influence perceptions of organizational change, particularly in international acquisitions (e.g. Stahl et al, 2012).…”
Section: Limitations and Implications For Researchmentioning
confidence: 99%
“…The definition of credibility is similar to that of trust: belief that the actions firms take can produce a positive income for investors (Almer et al, 2008;Chan, Huang, & Ng, 2008). Subjects were asked to respond to the statement: "We believe the information that the firm discloses" using a 7-point Likert scale anchored by "strongly disagree" and "strongly agree" corresponding to 1 and 7.…”
Section: Experimental Tasksmentioning
confidence: 99%
“…Leader-member exchange . China Trust in leadership has become one of the most pivotal factors in management research and practice because of its critical effect on employees' attitudinal and behavioral outcomes (Chan, Huang, & Ng, 2008;Dirks & Ferrin, 2001Mayer, Davis, & Schoorman, 1995;Schoorman, Mayer, & Davis, 2007). This, in turn, tends to shape the overall effectiveness of an entire organization due to the pivotal role of leadership (Bass, 1985;Lapidot, Kark, & Shamir, 2007;Podsakoff, MacKenzie, Moorman, & Fetter, 1990;Rousseau, Sitkin, Burt, & Camerer, 1998;Wong, Ngo, & Wong, 2003).…”
mentioning
confidence: 99%